2019
DOI: 10.3851/imp3379
|View full text |Cite
|
Sign up to set email alerts
|

An Expanded HIV Care Cascade: ART Uptake, Viral Load Suppression and Comorbidity Monitoring among Adults Living with HIV in Asia

Abstract: Background: Comprehensive treatment and clinical management are central to improving outcomes for people living with HIV (PLHIV). We explored trends in HIV clinical care, treatment outcomes, and chronic kidney disease (CKD) and diabetes monitoring. Methods: We included patients ≥18 years in care at ten clinical sites in eight Asian countries. Proportions of patients on antiretroviral therapy (ART), with annual viral load, and with viral load suppression (VLS; <1,000 copies/ml) were estimated by year for 2011- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…However, in many LMICs, the regularity of VL testing remains suboptimal. A recent study from Asia of 31,346 PLHIV (with > 60% of the data originating from India) showed that VL testing was performed less than annually in > 50% of PLHIV [ 17 ]. At present, NACO recommends CD4 monitoring among adult PLHIV on second-line ART with CD4 count < 350 cells/mm 3 in addition to 6-monthly VL testing [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in many LMICs, the regularity of VL testing remains suboptimal. A recent study from Asia of 31,346 PLHIV (with > 60% of the data originating from India) showed that VL testing was performed less than annually in > 50% of PLHIV [ 17 ]. At present, NACO recommends CD4 monitoring among adult PLHIV on second-line ART with CD4 count < 350 cells/mm 3 in addition to 6-monthly VL testing [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study of its kind. Previous studies on the AIDS epidemic in the Asia-Pacific region, [23][24][25][26] particularly Jong et al, observed that the rates of AIDSrelated and non-AIDS-related mortality in the Asia-Pacific cohorts decreased from 1999 to 2018 and that the risk for non-AIDSassociated deaths was higher in the high-income countries, compared to the lower-middle income countries. 26 In contrast, we found that the HIV burden in the Asia-Pacific region was highest in the low SDI group, and the incidence of HIV was highest among those in the 20−30 years age group.…”
Section: Discussionmentioning
confidence: 97%
“…A study conducted by Mckinney and colleagues showed that zidovudine exposure to children can cause anaemia and lactic acidosis which may affect breathing patterns (Mckinney et al,1991). Long term survivors of HIV who were through antiretroviral therapy (ART) showed several pathologies such as metabolic, lipid, cardiovascular and neurological disorders (Bijker et al, 2020). Another study conducted by Bertrand and colleagues showed that long term use of ART may result in cerebral vascular toxicity (Bertrand et al, 2019).…”
Section: Exposure Pathways and The Effects Of Arvds In Humans And Aqu...mentioning
confidence: 99%